The U.S. Congress : a very short introduction - Ritchie, Donald A., 1945- (New York, NY : Oxford University Press, 2023)
The unprecedented politics of the past four years, culminating in the mob attack on the U.S. Capitol on January 6, 2021, underscore the need for a new edition of 'The U.S. Congress: A Very Short Introduction.' The previous editions explored the essential necessity of compromise to accomplish anything significant in the legislative arena, but recent events show that political polarization has hardened and produced gridlock. This new edition explains how the parties have changed and how that has affected both the House and Senate.
This edition also issued in print: 2023.
Previous edition: 2016.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on December 16, 2022).
Keywords: United States. -- Congress; Politics and Government; Politics & government